A simplified and accurate method for the analysis of urinary metabolites of testosterone‐related steroids using gas chromatography/combustion/isotope ratio mass spectrometry. (20th June 2013) - Ouellet, Alexandre; LeBerre, Nicolas; Ayotte, Christiane
Abstract : RATIONALE: The analysis of urinary metabolites of testosterone‐related steroids through the measurement of their carbon isotopic signature (δ 13 C) by gas chromatography/combustion/mass spectrometry (GC/C/IRMS) is a confirmation method employed in doping control analyses. Stringent analytical conditions are essential to an accurate and precise analysis as well as the proper selection of the metabolites, which forms the basis of the refined method presented in this paper. METHODS: In a simplified approach, following enzymatic hydrolysis and extraction from a relatively low volume of urine sample, a one‐step high‐performance liquid chromatography (HPLC) purification was developed for seven diagnostic urinary metabolites (TS) including testosterone itself, dehydroepiandrosterone, 5α‐ and 5β‐androstanediol, epitestosterone, androsterone, etiocholanolone and two endogenous reference compounds (ERC), 5β‐pregnanediol and 5α‐androst‐16‐en‐3β‐ol. These steroids were pooled in three fractions and analyzed as such. With regards to the GC/C/IRMS analysis, a multi‐level isotopic calibration using the 'identical treatment' principle was created. RESULTS: The proposed isotopic calibration yielded results for purified reference steroids with a precision ≤0.15 and accuracy of ≤0.30 ‰ (between‐assay, n = 26). Compared to other common endogenous reference compounds, those selected in this study had δ 13 C values close to the target metabolites which, along with the proposed isotopic calibration, produced narrow reference intervals within ± 3‰ for most diagnostic TS‐ERC pairs, in compliance with the requirements of the World Anti‐Doping Agency. CONCLUSIONS: These carefully controlled analytical conditions are compatible with routine operations, affording accurate and precise results for the more diagnostically relevant metabolites such as testosterone itself and the 5α‐ and 5β‐androstanediols. The values of the TS‐ERC pairs measured in reference populations are described and the results from the routine testing of several hundreds of athletes' samples are discussed. Robust, this technique permitted the detection of adverse findings that would have been missed had these low level metabolites not been analyzed. Copyright © 2013 John Wiley & Sons, Ltd.